2020
DOI: 10.3390/v12111250
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analyses of Bovine Foamy Virus-Encoded miRNAs Reveal the Importance of a Defined miRNA for Virus Replication and Host–Virus Interaction

Abstract: In addition to regulatory or accessory proteins, some complex retroviruses gain a repertoire of micro-RNAs (miRNAs) to regulate and control virus–host interactions for efficient replication and spread. In particular, bovine and simian foamy viruses (BFV and SFV) have recently been shown to express a diverse set of RNA polymerase III-directed miRNAs, some with a unique primary miRNA double-hairpin, dumbbell-shaped structure not known in other viruses or organisms. While the mechanisms of expression and structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Elimination of the whole miRNA cassette from non-coding sequences in the U3 region of the long terminal repeats (LTRs) does not grossly affect structural protein expression, processing and particle release but it does impair overall BFV fitness and replication competence. These data indicate that the miRNAs do not play an obvious or prominent role in FV assembly and release [ 66 ].…”
Section: The Viral Machinery and Cellular Partners Of Fv Particle mentioning
confidence: 99%
“…Elimination of the whole miRNA cassette from non-coding sequences in the U3 region of the long terminal repeats (LTRs) does not grossly affect structural protein expression, processing and particle release but it does impair overall BFV fitness and replication competence. These data indicate that the miRNAs do not play an obvious or prominent role in FV assembly and release [ 66 ].…”
Section: The Viral Machinery and Cellular Partners Of Fv Particle mentioning
confidence: 99%
“…Therefore, although we did not search for the target genes of FFV-derived miRNAs in the present study, it is important to predict target genes when reliable target gene prediction tools become available in cats. Since previous studies reported that FV-derived miRNAs, such as SFVcae, SFVmfu, and BFV, suppress genes related to immune responses and tumor suppression in the host, it is possible that FFV-derived miRNAs also act on these metabolic pathways and help FFV infect hosts ( Kincaid et al , 2014 ; Cao et al , 2020 ; Hashimoto-Gotoh et al , 2020 ). In addition, an evaluation of infectivity using the miRNA deletion mutants of BFV showed that BFV-derived miRNAs contributed to improved infection efficiency ( Cao et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since previous studies reported that FV-derived miRNAs, such as SFVcae, SFVmfu, and BFV, suppress genes related to immune responses and tumor suppression in the host, it is possible that FFV-derived miRNAs also act on these metabolic pathways and help FFV infect hosts ( Kincaid et al , 2014 ; Cao et al , 2020 ; Hashimoto-Gotoh et al , 2020 ). In addition, an evaluation of infectivity using the miRNA deletion mutants of BFV showed that BFV-derived miRNAs contributed to improved infection efficiency ( Cao et al , 2020 ). Therefore, studies using miRNA deletion mutants will provide novel insights into the biological functions of FFV-derived miRNAs in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, FV encoded micro-RNAs (miRNAs) as shown in BFV [ 127 ] and SFVs [ 128 ] could act as regulators of the innate immune response. BFV miR-BF2–5p can suppress the expression of IFN-β and NF-kB mRNAs by targeting Ankyrin Repeat Domain 17 (ANKRD17), an upstream regulator in the innate immune system and Bax-interacting factor 1 (Bif-1, official name SH3GLB1) [ 129 ].…”
Section: Innate Immune Sensing Of Foamy Virusesmentioning
confidence: 99%